(untitled) (In situ, 2025)
In 2024, archaeological research continued at the Crkvina site in Šopot, near Benkovac. During this year’s campaign, conducted by the Benkovac Heritage Museum in cooperation with the Department of Archaeology of the University of Zadar, research continued on the graves in the area west of the church. This is a multi-layered cemetery with different types of graves, from burials in simple earthen pits to graves lined with stone slabs and amorphous stones. In addition to other graves, a stone structure representing a smaller burial plot was found and explored at the site, within which two graves with stone lining were found, placed one above the other, and four more similar structures were discovered that still need to be explored.